2022
DOI: 10.3389/fimmu.2021.786738
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE and IgG4 Profiles of House Dust Mite Components in Allergen-Specific Immunotherapy

Abstract: BackgroundAllergen immunotherapy (AIT) can induce immune tolerance to allergens by activating multiple mechanisms, including promoting IgG4 synthesis and blunting IgE production. However, the longitudinal data of sIgE and sIgG4 to allergen components during AIT are limited.ObjectiveWe sought to investigate the persistence and evolution of sIgE and sIgG4 against house dust mite (HDM) components during AIT and explore their correlation with clinical responses.MethodsSixty allergic rhinitis (AR) with/without asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Besides IgE, we were particularly interested in the identification of IgG4 epitopes induced during AIT. The observed increase in IgG4 binding to HDM peptides/epitopes as well as in IgG4 amplitude during SLIT in our study is in line with previous observations of increased allergen-specific IgG4 levels during immunotherapy for house dust mite as well as other allergen sources [ 13 , 14 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Besides IgE, we were particularly interested in the identification of IgG4 epitopes induced during AIT. The observed increase in IgG4 binding to HDM peptides/epitopes as well as in IgG4 amplitude during SLIT in our study is in line with previous observations of increased allergen-specific IgG4 levels during immunotherapy for house dust mite as well as other allergen sources [ 13 , 14 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…There is a plethora of literature that evaluates molecular profiles of IgE and IgG4 recognition during AIT [ 13 , 14 ], especially subcutaneous. Epitope mapping goes back approximately 30 years [ 15 ], some previous works have identified epitopes in HDM allergens, such as Der p 5 [ 16 ], Der p 7 [ 17 ], Der p 2 [ 18 , 19 ], Der p 39 [ 20 ], and Blo t 11 [ 21 ] to characterize IgE only or IgE and IgG binding sites by various methods.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with allergic rhinitis and dust mite allergy who received SLIT showed a shift from Th2 to Th1 mode, with a decrease in the levels of Th2-secreting cytokines in peripheral blood mononuclear cells (IL-4, IL-5, IL-13) [23]. Secondly, SLIT can consistently reduce allergen-speci c IgE synthesis and contribute to the ongoing production of IgG4-blocking antibodies [24]. A multicenter randomized controlled open trial found that after 12 months of treatment, patients in the SLIT group showed a signi cant increase in serum-speci c IgG4 levels compared to controls, while the IgE/IgG4 ratio showed a signi cant decrease compared to baseline [25].…”
Section: Discussionmentioning
confidence: 99%
“…This change is accompanied by induced blocking antibodies (particularly, of the subclass IgG4) [ 107 ]. The sIgE/tIgE ratio is often increased following AIT treatment [ 108 109 110 111 112 ], however, no changes are observed when evaluated less than 2 years of AIT treatment [ 113 ]. The blocking activity of IgG antibodies maintains unchanged for at least 2 years of discontinuation of AIT, despite the reduction in the IgG1 and IgG4 levels [ 114 ], suggesting long-term immune tolerance following cessation of AIT treatment.…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%